Impact of Robotic Circular Wood Processing: Lessons from the “One Plank” Challenge – using the AUAS Circular Wood KPI Framework - Schoen, Tony; Griffioen, Simon; Malé-Alemany, Marta; Rodrigues, Manuel; Kiestra, Mirjam (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
Wood is an increasingly demanded renewable resource and an important raw material for construction and materials. Demands are rising, with a growing attention for re-use and upcycling, opening up opportunities for new business models, empowered by the use of digital design and technologies. A KPI framework was developed to evaluate the environmental, social, and economic aspects of using recycled wood in robotic manufacturing. This paper explores the use of this framework, focusing on a case study: the "One Plank" Challenge. The study reveals that environmental gains from using waste wood are comparable to production burdens, with significant variation depending on wood type. Production time, encompassing both human and robotic aspects, significantly impacts cost-effectiveness. The findings underscore the importance of considering lifecycle impacts in promoting sustainable robotic manufacturing practices.